Games and Rules Game Mechanics for the »Magic Circle« - Suter, Beat; Kocher, Mela; Bauer, René (Edition Medienwissenschaft, 2019)
Why do we play games and why do we play them on computers? The contributors of »Games and Rules« take a closer look at the core of each game and the motivational system that is the game mechanics. Games are control circuits that organize the game world with their (joint) players and establish motivations in a dedicated space, a »Magic Circle«, whereas game mechanics are constructs of rules designed for interactions that provide gameplay. Those rules form the base for all the excitement and frustration we experience in games. This anthology contains individual essays by authors with backgrounds in Game Design and Game Studies, who lead the discourse to get to the bottom of game mechanics in video games and the real world.